2014
DOI: 10.1016/j.biopsycho.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal cortisol patterns and psychiatric symptoms in pregnancy: Short-term longitudinal study

Abstract: Alteration in the HPA axis is a robust biomarker of anxiety and depression in adults, but questions remain about this association in pregnancy. We examined the longitudinal links between diurnal cortisol and mood symptoms from self-report questionnaire and diagnostic interview in an ethnically diverse, psychosocially at-risk sample of 101 women at mid-pregnancy and early third trimester. There were modest but significant associations between depression and elevated cortisol, indexed by a decreased morning leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 53 publications
1
70
2
Order By: Relevance
“…1,4,34,48 However, it is important to note that investigations of maternal depression and cortisol in pregnancy have reported mixed results. 12,13,[49][50][51][52][53][54] Nonetheless, it has been suggested that biological markers of prenatal stress may be better indicators of offspring outcomes than selfreport measures. 34 Thus, we expected that maternal cortisol would significantly predict infant NR3C1 IF and BDNF IV methylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,4,34,48 However, it is important to note that investigations of maternal depression and cortisol in pregnancy have reported mixed results. 12,13,[49][50][51][52][53][54] Nonetheless, it has been suggested that biological markers of prenatal stress may be better indicators of offspring outcomes than selfreport measures. 34 Thus, we expected that maternal cortisol would significantly predict infant NR3C1 IF and BDNF IV methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of prenatal depression have suggested that clinical diagnoses correlate more reliably with biological markers of depression, such as awakening cortisol, than do self-report measures. 12 Therefore, using clinical diagnoses to define the depressive symptom group may have revealed a potential relationship between depressed mood, maternal glucocorticoids, and epigenetic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is largely because in non-pregnant populations symptoms of depression are associated with cortisol hyper-secretion (Bhagwagar et al, 2005;Cowen, 2002;Herbert, 2013). However, data linking symptoms of mood disturbance in pregnancy with changes in maternal HPA function have been mixed, with evidence both for (Giesbrecht et al, 2012;Murphy et al, 2014;O'Connor et al, 2013;Obel et al, 2005) and against (Hellgren et al, 2013;Pluess et al, 2012) cortisol hyper-secretion. One possible explanation for the disparate findings is that cortisol levels rise throughout pregnancy, regardless of mood state, due to the release of corticotrophin-releasing hormone (CRH) from the placenta.…”
Section: Introductionmentioning
confidence: 94%
“…Maternal depression during pregnancy has been associated with elevated mid-pregnancy corticotrophin releasing hormone (Rich-Edwards et al 2008;O'Keane et al 2011) and cortisol levels (Field et al 2006(Field et al , 2008, with altered diurnal pattern of cortisol secretion in the second trimester (O'Keane et al 2011;O'Connor et al 2013b), and with increased urinary cortisol at the middle to end of the third trimester (27-35 weeks) (Lundy et al 1999). Evidence is less clear when examining the relationship between maternal anxiety and/or symptoms of stress and changes in the maternal HPA axis.…”
Section: Changes In Circulating Levels Of Maternal Hormones During Prmentioning
confidence: 96%